Bioaccessibility Evaluation of Soymilk Isoflavones with Biotransformation Processing - Gabriela Alves Macedo; Cíntia Rabelo e Paiva Caria; Paula de Paula Menezes Barbosa; Marina Rodrigues Mazine; Alessandra Gambero (Foods, 2023)
Soy isoflavones are considered important sources of bioactive compounds, but they are poorly absorbable, due to their large hydrophilic structures. Some biotransformation strategies have been used to convert the glycosidic form into aglycones, making them available for absorption. This study evaluated the potential of enzymatic and/or microbial fermentation combined bioprocesses in a soymilk extract before and after gastrointestinal in vitro digestion. Commercial β-glucosidase (ET) and a mix of commercial probiotics (F) containing Lactobacillus acidophilus, Lactobacillus casei, Lactococcus lactis, Bifidobacterium bifidum, and Bifidobacterium lactis were used to biotransform the soymilk phenolic extract. An isoflavone profile was identified using HPLC-DAD, total phenolic content was identified using the Folin–Ciocalteu test, and antioxidant capacity was identified using ORAC and FRAP. Soymilk enzymatically treated (ET) followed by microbial fermentation (ET + T) resulted in better conversion of glycosylated isoflavones (6-fold lower than control for daidzin and 2-fold for genistin) to aglycones (18-fold greater than control for dadzein and genistein). The total phenolic content was increased (3.48 mg/mL for control and 4.48 mg/mL for ET + T) and the antioxidant capacity was improved with treatments of ET + T (120 mg/mL for control and 151 mg/mL with ORAC) and with FRAP (285 µL/mL for control and 317 µL/mL). After the in vitro digestion, ET + T samples resulted in a higher content of genistein (two-fold higher than control); also, increases in the total phenolic content (2.81 mg/mL for control and 4.03 mg/mL for ET + T) and antioxidant capacity measured with ORAC were greater compared to undigested samples. In addition, the isolated microbial fermentation process also resulted in positive effects, but the combination of both treatments presented a synergistic effect on soy-based products.